2018
DOI: 10.1161/jaha.117.008252
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Risk of All‐Cause and Cardiovascular Disease Mortality Over 20‐Year Follow‐up: Results From the BLSA

Abstract: BackgroundCognitive impairment may increase the risk of all‐cause and cardiovascular disease (CVD) mortality. This study examined the association between cognitive function and risk of all‐cause and CVD mortality among the elderly in Beijing, China.Methods and ResultsA total of 1996 participants aged ≥55 years at baseline were enrolled from the BLSA (Beijing Longitudinal Study of Aging). Cognitive function was assessed using the Mini‐Mental State Examination (MMSE), and participants were categorized as: <18, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 27 publications
2
35
0
3
Order By: Relevance
“…The previous study also found that the strength of this relationship differs due to the cause of death [19]. A strong link between CVD death and cognitive functions might be due to common cardiovascular risk factors [2,15].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The previous study also found that the strength of this relationship differs due to the cause of death [19]. A strong link between CVD death and cognitive functions might be due to common cardiovascular risk factors [2,15].…”
Section: Discussionmentioning
confidence: 84%
“…Some studies did not find a significant difference between men and women in this association [13]. Another previous study ascertained that the risk was higher in the male group [15].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Однако результаты этих исследований в отношении пожилого контингента носят зачастую противоречивый характер. Так, в исследовании Ji An, et al были показаны достоверные ассоциации между когнитивными нарушениями и смертностью от всех причин и ССЗ [21].…”
Section: Discussionunclassified
“…An и соавт. [10] изучалась прогностическая роль КН, выявленных с помощью КШОПС, в отношении неблагоприятных кардиоваскулярных событий. Авторами был проведен анализ исследования BLSA (Beijing Longitudinal Study of Aging), включавшего 1996 участников, средний возраст которых составлял 69 лет.…”
unclassified